Analysis of the Impact of County-Levelization on Economic Growth and Public Service Development Based on Panel Data - Wangteng Xu; Shaojian Wang (Discrete Dynamics in Nature and Society)
County-levelization has become an important vane and propeller of urban spatial development, which is closely related to economic development and public service development. County-levelization can effectively broaden the geographic scope of urban areas, enhance urban functions, and implement strategic planning measures for metropolitan areas. But what impact will such reform have on economic growth and public service development? What is the effect of the current policy of “abolishing counties and establishing districts” in the implementation process? Should the policy of “abolishing counties and establishing districts” be promoted or not? Based on a panel of 453 counties in China, this paper uses DID to analyze the impact of county zoning on county economic growth and public service development and uses PSM-DID to test the robustness. The study shows that county-levelization in China has had a positive effect on economic growth, but in the areas of education and health/public services, such reforms have only had a “squeeze effect” with minimal effect.